The Impact of Personal Factors on Innovative Work Behavior of Employees at Commercial Joint-Stock Banks in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2025)
Innovation is important in improving employee performance and enhancing the organization’s competitiveness. This article analyzes the system of factors within the personal factor group that influence the innovative work behavior of bank employees, including employee creativity, confidence in innovative capabilities, and job engagement. The article also examines the impact of the innovative behavior of bank employees on their job performance. The article uses a quantitative research method with survey data from 250 employees of a joint-stock commercial bank—research on data analysis and processing using PLS-SEM software version 3.0. The research results show that all factors influence employees’ innovative work behavior; confidence in employees’ innovative capabilities has the most significant impact, followed by creativity and job engagement. The innovative work behavior of bank employees also significantly affects their job performance outcomes. From there, the research proposes solutions to help bank employees perform their jobs better by promoting innovative work behaviors.